Evolutionary History of Major Chemosensory Gene Families across Panarthropoda. (4th August 2020) - Vizueta, Joel; Escuer, Paula; Frías-López, Cristina; Guirao-Rico, Sara; Hering, Lars; Mayer, Georg; Rozas, Julio; Sánchez-Gracia, Alejandro
Abstract: Chemosensory perception is a fundamental biological process of particular relevance in basic and applied arthropod research. However, apart from insects, there is little knowledge of specific molecules involved in this system, which is restricted to a few taxa with uneven phylogenetic sampling across lineages. From an evolutionary perspective, onychophorans (velvet worms) and tardigrades (water bears) are of special interest since they represent the closest living relatives of arthropods, altogether comprising the Panarthropoda. To get insights into the evolutionary origin and diversification of the chemosensory gene repertoire in panarthropods, we sequenced the antenna- and head-specific transcriptomes of the velvet worm Euperipatoides rowelli and analyzed members of all major chemosensory families in representative genomes of onychophorans, tardigrades, and arthropods. Our results suggest that the NPC2 gene family was the only family encoding soluble proteins in the panarthropod ancestor and that onychophorans might have lost many arthropod-like chemoreceptors, including the highly conserved IR25a receptor of protostomes. On the other hand, the eutardigrade genomes lack genes encoding the DEG-ENaC and CD36-sensory neuron membrane proteins, the chemosensory members of which have been retained in arthropods; these losses might be related to lineage-specific adaptive strategies of tardigrades to survive extreme environmental conditions. Although the results of this study need to be further substantiated by an increased taxon sampling, our findings shed light on the diversification of chemosensory gene families in Panarthropoda and contribute to a better understanding of the evolution of animal chemical senses.